Social Movement In Danielle Steel Journey Novel (2000): A Sociological Approach - NURITA, DIAN (2012)
This research paper elaborates the social movement of Madeleine in Danielle steel's Journey that is analyzed through sociological approach. The objectives of the research are to analyze the structural elements of the novel and to analyze the novel based on a sociological approach. This research belongs to a descriptive qualitative research. The data of the research is the novel entitled Journey. Whereas the data source comes from both primary data source which is the novel itself and secondary data source such as biography of the author, websites and other sources. The method to analyze the data is descriptive analysis. Based on the analysis toward the novel, the writer concludes that the social movement of Madeleine is shown by the structural elements which build the novel such as characters, setting, plot, theme, and point of view and sociological analysis. The writer also finds that the major character is encouraged to move her life after she joins in a woman organization. She realizes that she has ability and power to get her freedom in her life from being abused, both physically and psychologically.